Political cognition. Can scientific paradigms change cognitive status of anti-Semitism and the Holocaust in the history of the Jewish people? = Polityka poznania. Czy paradygmaty naukowe mogą zmieniać kognitywny status antysemityzmu oraz Holocaustu w dziejach narodu żydowskiego? - Młyńczyk, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this article is to look at selected positions devoted to issues of historical experience of the Jewish people for their research strategy and their corresponding or lack of dominant research paradigms. The basic intention is to indicate the path of political science to know the history of the nation, through limited exemplification as a response to the absolutization of the research results before they are published to be limited exclusively to the study of the Jews, as the people, especially experienced by the history, which enforces appropriate research approaches.
Keywords: antysemityzm; Holocaust; Żydzi; polityka poznania; paradygmat; anti-Semitism; political cognition; Jews; paradigm